THE STATUS OF RESEARCH FUNDING IN THE RUSSIAN FEDERATION AT THE MODERN STAGE - M. D. Khabib; M. Yu. Teplyakova; E. V. Krasnov (Вестник университета, 2019)
The topic of the article is the importance and features of science financing in the Russian Federation. The results of a comparison of macroeconomic indicators of science financing in different countries have been presented. The system of indicators used in the Russian statistical practice has been considered. The sources of funding for the sectors of science have been analyzed. Particular attention has been paid to the study of domestic research and development costs in the context of various groups: by ownership, by economic activity, by type of expenditure, by areas of science, technique and technology, by socio-economic goals, areas of economic development and research areas.